Evaluation of a possible association between allergic rhinitis and depression, suicidal ideation, and suicide attempts among adolescents based on a nationwide cross-sectional study. (July 2020) - Kim, Joo Young; Han, Young Joo; Lee, Ju Suk; Lee, Jun Hwa; Jo, Seon Hui; Kim, Sung Hoon
Abstract: Objective: We assessed associated factors for depression and suicidality among adolescents with allergic rhinitis (AR) by analyzing data from annual Korea Youth Risk Behavior Web-based Surveys (KYRBSs) completed from 2007 to 2017. Methods: Data from the KYRBS were obtained from a stratified, multistage, clustered sample. Using self-reported questionnaires, students provided yes-or-no answers to questions addressing their doctor-diagnosed AR and self-experienced depression, suicidal ideation and suicide attempts. Associated factors for depression and suicidality were identified by logistic regression models after controlling for potential confounding factors. A total of 818, 684 adolescents were targeted, and 788, 411 adolescents completed the survey. Results: An AR diagnosis was reported in 30.8% of respondents. Among respondents with AR, 34.5%, 18.4%, and 4.2% reported depression, suicidal ideation, and suicide attempts, respectively. Adolescents with AR were significantly more likely to have negative mental health status, including suicidality than adolescents without AR. After multiple logistic regression analyses, perception of stress was most strongly associated with depression and suicidal ideation (adjusted odds ratio: 5.16 [95% confidence interval; 5.04–5.28], 4.81 [4.65–4.98], respectively). For suicide attempts, subjective unhappiness was most strongly associated (3.63 [3.47–3.79]) among adolescents with AR. Presence of AR itself was also associated with depression and suicidality (1.10 [1.08–1.11], 1.08 [1.06–1.10], 1.05 [1.01–1.08], respectively). Conclusion: Adolescents with AR had significantly greater prevalence of depression and suicidality. Multidisciplinary team approaches, including psychological support, may be needed to prevent suicide among adolescents with AR, especially those with identifiable risk factors.